LIFE STRUGGLE OF THE PROTAGONIST IN NARA LAHMUSI’S NOVEL A SKY FULL OF STARS - Dewi, Suci Mulia; Wulan, Sri (Universitas Islam Sumatera Utara, 2025)
This study investigates the life struggles experienced by the protagonist in A Sky Full of Stars by Nara Lahmusi, focusing on her journey toward achieving personal dreams while simultaneously addressing familial obligations. The research aims to analyze the internal and external factors that shape the protagonist's hardships. Internal factors include her perfectionism, strong sense of self-priority, and inner ambition, which drive her personal goals but also contribute to emotional and psychological pressure. In contrast, external factors such as economic limitations and societal expectations impose constraints that complicate her efforts. By examining the interaction between these two dimensions, the study reveals how the protagonist's development is influenced by the dynamic tension between individual aspiration and external reality. The findings suggest that the complexity of her struggle lies in the convergence of personal desires and external demands, which not only affects her decisions but also frames the broader thematic structure of resilience and self-determination in the novel.